Panchayati Raj System in Haryana State: Examining the Panchayati Raj System and PRIA's intervention in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article tries to cover a few parts of Panchayati Raj System in Haryana. Through this system a three level Panchayati Raj System was set up in each locale of Haryana. It has three indispensable components gram panchayat, panchayat samiti and zila panchayat. In this examination we learn about the History of Panchayati Raj in the Haryana, PRIA's intercession in detail and it is presumed that the Three years' experience of reinforcing PRIs in Haryana combined with an evaluation of our impact in the record has given us helpful bits of knowledge for arranging our future mediations.